Paper 88: The Natural History of Anterior Shoulder Instability in Patients Over the Age of 50: A Population Based Study. Issue 7 (30th July 2022) - Wilbur, Ryan; Song, Bryant; Reinholz, Anna; Till, Sara; Okoroha, Kelechi; Krych, Aaron; Camp, Christopher; Smartt, Anne
Objectives: Anterior shoulder instability (ASI) is a well-studied topic in young patients, however there is a dearth of knowledge about older patients with this pathology. The goals of this study were to describe patient demographics, injury characteristics and outcomes in patients >50 years old with anterior shoulder instability along with historical trends in diagnosis and treatment. Methods: An established geographic database was used to identify 179 patients who experienced new onset anterior shoulder instability after the age 50 between 1994-2016. Mean age was 59.7 years, mean BMI was 31.3 and 54.2% were female. The dominant arm was involved in 62.2% of instability events. 26.8% of our study population were laborers and 50% reported current or former smoking habits. The primary etiology for ASI involved trauma in 96.6% of cases. Comparative analysis was performed to identify differences between age groups. Mean follow up time was 11 years. Results: The overall incidence of ASI in our study population was 28.8/100, 000 person years with the highest incidence in the age cohort 60-64 at 38.9/100, 000 person years. At initial presentation, 73% of all patients were found to have a lesion apparent on either XR or MRI. Rotator cuff tears were found in 92.4% of all patients undergoing MRIs. 26.2% ultimately progressed to surgery at a mean time of 1.57 years after injury. 53% of all surgical procedures involved a rotator cuff repair whereas only 25% were performed for instability. In terms of historical trends, the one-year rate of obtaining an MRI after an ASI event has increased from 10% in the late 1990s to 46% in 2015-16. Similarly, the one-year rate of performing surgery has increased from 5.1% to 47% from 1994-1999 to 2015-2016. Conclusions: In our cohort, patients over the age of 50 with ASI were found to often have concomitant pathology on imaging, however only ¼ of all patients required surgery. Although the rate of ASI has stayed relatively stable over the last 20 years, the rate of obtaining an MRI and of surgical management has increased. Figure 1. Incidence of Anterior Instability by age